SIMULATION ANALYSIS OF A NEONATAL UNIT WITH COMPLEX PATIENT FLOW PATTERNS – AN ENHANCED MODEL FOR CAPACITY PLANNING - Perera, Terrence Sisira; Calis, Banu (The South African Journal of Industrial Engineering, 2022)
Steadily increasing demand requires neonatal units and networks to improve their overall capacities. Given the operational complexities involved, simulation is a popular choice for capacity planning studies. , For efficient model building, simulation exercises typically assume unidirectional flow of patients i.e., infants progressively move to lower levels of care. Patient flows are, however, much more complex i.e., time-to-time patients may require a higher level of care than the current level of care. This paper argues that bi-directional flow modelling is required to produce accurate capacity estimates thereby improving the quality decision making.